Acquisition of the photoplethysmographic signal for different physiological conditions and varying age groups - Shah, Mansoor Hussein (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This research explores the effect of physical conditions of varying age groups on photoplethysmographic (PPG) acquired through using an IR sensor. Easy Pulse Sensor Module interfaced to Arduino processing board are used to capture the PPG signal of subjects of known age group under similar working indoor environmental conditions and time of the day following strictly the university ethical rules. The Easy Pulse Analyzer processes the data so acquired and CoolTerm software based Graphical User Interface (GUI). The PPG sample data from the volunteers in the standing, lying, and jogging at the same spot conditions are examined and compared. Likewise, the PPG signals are obtained from the volunteers within the age group of 20s and 50s under similar different physiological conditions and a comparison is made in order to examine the behaviour of the PPG signal for varying age groups. The Kubios HRV biomedical software is used to study the PPG signals and report sheets are generated. The results are examined in terms of varying Heart Rate Variability (HRV) and Power Spectral Density (PSD) values. The results show the variation of the PPG signal in terms of its HRV, low frequency (0.04-0.15Hz) and high frequency (0.15-0.4Hz), LF/HF components and Power Spectral Density (PSD) results for different physiological conditions of varying age groups. The results also show that the values of HRV and HF components increase during the transition from sympathetic to parasympathetic physiological conditions. Furthermore, the PSD related components like absolute power (ms2) and percentage power (% power) are also increased with the HF values and HF components.